Small loans, big dreams : how Nobel prize winner Muhammad Yunus and microfinance are changing the world - Counts, Alex.; Counts, Alex (Hoboken, N.J. : John Wiley & Sons, 2008)
This book attempts to bring the microfinance story, one that has revolutionized global antipoverty effort, down to a human level.
Originally published in 1996 by Times Books as: Give us credit.
Includes bibliographical references (p. 387-392) and index.
osa 09/05/13, ijb 26/02/2019
Loans
Keywords: Yunus, Muhammad; Banks and banking; Rural poor; Poor; Microfinance